Descriptive Study Midwives Perception of Giving Sinovac Vaccine in Pregnant Women to Prevent Transmission of Covid-19 - Yayuk Eliyana; Layla Imroatu Zulaikha; Qurratul A'yun (JURNAL KEBIDANAN, 2024)
During the Covid-19 pandemic, routine maternal and infant health services such as pregnancy checks, there are restrictions to reduce the risk of transmission in covid 19. This research is descriptive research. The sampling technique was a total sampling with the number of samples as many as 20 midwives in the Pamekasan City Area. The analysis used in this study was a univariate analysis using frequency distribution tables. The results showed that almost all midwives have never given sinovac vaccine to pregnant women to prevent transmission of the Covid-19 virus, sinovac vaccine administration in pregnant women most midwives consider it necessary, about 60% of midwives have a perception that the right time for sinovac vaccine administration in pregnant women is in the second trimester. It is hoped that there will be an increase in the scope of sinovac vaccine administration in pregnant women so as to prevent the transmission of the Covid-19 virus in pregnant women.